PENGARUH DISIPLIN PEGAWAI NEGERI SIPIL TERHADAP EFEKTIVITAS PENYELENGGARAAN PEMERINTAHAN Studi Pada Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Bolaang Mongondow Selatan - MANE, NADHILLAH AMALIAH; RORONG, ARIE; MAMBO, RULLY (JURNAL ADMINISTRASI PUBLIK, 2019)
Building a state apparatus to be more efficient and effective is a strategic step in carrying out thegeneral tasks of government and national development in the framework of implementing effectivegovernance. To create an effective government, the first step that must be taken is to improve the disciplineof Civil Servants. Because Civil Servants are the wheels of government that carry out their duties bothregional and central government. Therefore high discipline from Civil Servants will influence theeffectiveness of government administration. This research uses Quantitative research, which is trying toanswer the influence of Civil Servants Discipline variables on the Effectiveness of GovernmentAdministration. Data is collected by careful observation, including questionnaires in detailed contexts, aswell as in-depth interviews, as well as the results of the analysis. Scale statistics describes the average andstandard deviation of the dependent and independent variables, the average effectiveness of governance is22.50 mean with a standard deviation of 2013. the discipline average is 63.33 mean with a standarddeviation of 5.774. in the simple regression equation it can be seen that the regression direction coefficientis 0.281 and the constant coefficient (a) is 4.679. It is clear that the regression coefficient value (b) ispositive, which is 0.281. Y = 4,679 + 0,281X. Where every 1% increase in the value of the Discipline ofCivil Servants, the value of Government Organizational Effectiveness increases by 0.281 or 28.1% so thatit can be said that the direction of the influence of the Civil Servants Discipline variable (X) on theGovernment Implementation Effectiveness Variables (Y) is Positive.Keywords: Civil Servants Discipline, Government Organizational Effectiveness